Pabrikasi Membrane Electrode Assembly Menggunakan Metode Decal Transfer Dengan Variasi Ketebalan Katalis Platina-Titanium Dioksida Didukung Vulcan XC-72 - Manik, Luh Ary Putri; Joni, I Made; Suarda, Made; Astawa, Ketut; Sucipta, Made (Teknik Desain Mekanika, 2025)
Abstract Energy is very important in human life. Currently, most energy sources in Indonesia still depend on fossil fuels. The depletion of fossil energy sources and environmental problems are two major problems that will be faced if we continue to rely on fossil fuel-based energy. Therefore, the transition to green energy, such as hydrogen, is a major focus at the moment. Hydrogen can be converted into electricity using proton exchange membrane fuel cell (PEMFC) technology, where the membrane electrode assembly (MEA) is the key. MEA performance is influenced by several factors, one of which is the fabrication method used. The main focus of this study is to improve PEMFC performance through MEA fabrication using the decal transfer method with variations in the thickness of the Pt.TiO2/vulcan XC-72 catalyst. Sample 1 with anode and cathode thickness of 30?m, Sample 2 with anode thickness of 30?m and cathode of 40?m, and Sample 3 with anode thickness of 30?m and cathode of 50?m. Based on performance testing, Sample 1 showed the best results, which produced a voltage of 0.3?V. while samples 2 and 3 produced a lower voltage of 0.2?V. Lower thickness tends to produce MEA with better performance. This is because generally at a lower catalyst thickness it will produce a better interface relationship so that the three phase boundaries (TPB) zone is formed. Keywords: Decal Transfer, catalyst thicknes, Membrane Electrode Assembly